Prinsip Tolong-Menolong (I'anah) Sebagai Landasan Etika Transaksi Dalam Perbankan Syariah: The Principle of Mutual Assistance (I’anah) as the Ethical Foundation of Transactions in Islamic Banking - Alfianti, Balita; Sudrajat, Bayu; Asy-syifa, Luthfi Durori; Rozak, Muhammad Fathur; Nashrullah, Nashi; Pangestuti, Yosinta (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the principle of i’ānah as the ethical foundation for transactions within Islamic banking, utilizing a qualitative approach grounded in literature review and thematic analysis. The principle of i’ānah is conceptualized as the value of mutual assistance, serving as the moral cornerstone for all Islamic economic activities. By employing a qualitative methodology with a library research design and thematic analysis, this research conducts an in-depth examination of i’ānah as the ethical basis for Islamic banking transactions. The findings indicate that i’ānah functions not merely as an ethical guideline but also as a philosophical framework that reinforces the social orientation and justice inherent in Islamic banking transactions. An analysis of various classical and contemporary literature, alongside regulatory documents, demonstrates that integrating i’ānah values into Islamic banking products, services, and governance can enhance ethical compliance, strengthen accountability, and bolster institutional reputation. This study emphasizes the strategic urgency of implementing i’ānah values to fortify moral legitimacy and promote public benefit (maslahah) within Islamic financial practices. These findings pave the way for future research concerning the empirical measurement of i’ānah values regarding institutional behavior and customer perception.